Porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material as well as preparation method and application thereof
By preparing the positive electrode material of porous vanadium-based composite carbon nanofiber flexible zinc ion battery with beaded structure, the cyclic stability and conductivity problems of the positive electrode material of the aqueous zinc ion battery are solved, and efficient electrochemical performance improvement and volume expansion reduction are achieved. Suitable for a variety of battery applications.
Patent Information
- Application Number
- CN202411343571.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing water-based zinc ion battery positive electrode material has low cyclic stability, low electronic conductivity and volume expansion, which limits its prospects in high energy density applications.
The preparation method of the positive electrode material of porous vanadium-based composite carbon nanofiber flexible zinc ion battery is prepared by electrospinning a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinylpyrrolidone and polytetrafluoroethylene emulsion. The structure of vanadium trioxide-based composite carbon nanofibers is carbonized by heat treatment process to improve conductivity and stability.
It improves the cyclic stability and electronic conductivity of the electrode material, reduces volume expansion, improves electrochemical performance, and is suitable for the fields of water-based zinc ion batteries and other ion batteries.
Smart Images

Figure CN119162700A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and particularly relates to a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] With the increasing global demand for clean energy and the replacement of traditional fossil fuels, aqueous zinc-ion batteries are gradually becoming the focus of research and development due to their unique advantages; zinc is a widely available and low-cost metal, and the manufacturing cost of its batteries is much lower than that of traditional lithium-ion batteries, making the application of aqueous zinc-ion batteries in energy storage systems more economically feasible; secondly, metallic zinc has good corrosion resistance, ductility and fluidity, and aqueous zinc-ion batteries also have the above-mentioned excellent properties; aqueous zinc-ion batteries are safer than traditional lithium-ion batteries and are not prone to violent chemical reactions leading to thermal runaway or even spontaneous combustion; at the same time, aqueous zinc-ion batteries use aqueous or water-based electrolytes, and their fire and explosion risks are significantly reduced compared to organic solvents, making aqueous zinc-ion batteries more reliable and safe in large-scale energy storage systems, especially suitable for grid support and distributed energy systems; although the zinc metal negative electrode has a high specific capacity, due to the limitation of the positive electrode material, the energy density of aqueous zinc-ion batteries is still much lower than that of lithium-ion batteries, which limits the application prospects of aqueous zinc-ion batteries in high energy density applications.
[0003] At present, the existing positive electrode materials of aqueous zinc-ion batteries generally have low cycle stability, low electronic conductivity and volume expansion. Among them, the low cycle stability is manifested as follows: compared with traditional lithium-ion batteries, the cycle life of positive electrode materials of aqueous zinc-ion batteries is shorter and the stability is poorer; the low electronic conductivity is manifested as follows: the electronic conductivity of positive electrode materials of aqueous zinc-ion batteries is usually lower than that of lithium-ion battery materials, which in turn affects its charging and discharging speed and the overall performance of the battery; the volume expansion phenomenon is manifested as follows: during the charging and discharging process, the embedding and extraction of zinc ions in the electrode material will cause the volume expansion of the electrode, thereby affecting the battery performance and life. Therefore, there is an urgent need for a new type of rechargeable zinc-ion battery positive electrode material with a long cycle life, good stability, high electronic conductivity, and major application scenarios in the new energy field. Summary of the invention
[0004] In view of the technical problems existing in the prior art, the present invention provides a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material and a preparation method and application thereof, so as to solve the technical problems that the existing aqueous zinc ion battery positive electrode materials generally have low cycle stability, low electronic conductivity and volume expansion phenomenon.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: The present invention provides a method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, which is characterized by comprising: A pre-prepared uniform solution containing ammonium metavanadate, dihydrated oxalic acid, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is added into deionized water and subjected to ultrasonic treatment to obtain a spinning solution; Electrospinning the spinning solution to obtain composite fibers; The composite fibers are dried to obtain dried composite fibers; the dried composite fibers are heat-treated to obtain vanadium trioxide-based composite carbon nanofiber flexible electrode materials with a beaded structure, that is, porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode materials are obtained.
[0006] Furthermore, the mass ratio of the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion to deionized water is (0.4-0.9):1.
[0007] Furthermore, in the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion, the mass ratio of ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is 1:2:1:(1-6).
[0008] Furthermore, the preparation process of the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is as follows: Add PVP to deionized water and stir vigorously until uniform to obtain a PVP solution; ammonium metavanadate, oxalic acid and PVP solution are mixed and reacted to obtain a precursor solution; The precursor solution is subjected to ultrasonic treatment in an ice water bath. After the ultrasonic treatment is completed, polytetrafluoroethylene emulsion is added to obtain a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion.
[0009] Furthermore, in the process of electrospinning the spinning solution to obtain the composite fiber, the voltage is 12-35 kV, the ambient humidity is controlled at 40%-60%, the distance between the metal needle and the collector is 10-20 cm, and the temperature is controlled at 20-50°C.
[0010] Furthermore, in the process of electrostatic spinning the spinning solution to obtain the composite fiber, a non-woven fabric is used as a receiving member for the composite fiber.
[0011] Furthermore, the composite fiber is dried to obtain the dried composite fiber at a drying temperature of 60-80° C. and a drying time of 2-4 hours.
[0012] Further, the process of heat treating the dried composite fiber is as follows: The dried composite fiber is kept at 150-250°C for 2-4 hours at a heating rate of 2-10°C / min; then, the temperature is continued to rise at a rate of 2-10°C / min and kept at 250-350°C for 2-4 hours to obtain a flexible self-supporting composite nanofiber; Then, under a protective atmosphere, the flexible self-supporting composite nanofibers are kept at 650-750° C. for 4-6 hours at a heating rate of 2-10° C. / min to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure.
[0013] The present invention also provides a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, which is prepared by using the preparation method of the porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material.
[0014] The present invention also provides an application of a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material. The porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material is used in an aqueous zinc ion battery and serves as the positive electrode of the aqueous zinc ion battery.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material. The method comprises the following steps: mixing a uniform solution containing ammonium metavanadate, dihydrated oxalic acid, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion with deionized water to prepare a spinning solution, preparing composite fibers by an electrostatic spinning process, and drying and heat-treating the composite fibers to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure. The electrostatic spinning is performed using water as a solvent, which can reduce pollution during the spinning process and has the advantages of being safe and green. PVP is used as a flexible substrate support for a carbon source, and the PVP is carbonized by a heat treatment process. The carbonized PVP is used as a reinforcing agent and a conductive material to improve electrode stability. The precursor salt is used to generate active substances in the carbon skeleton in situ, thereby giving the carbon fiber a high-efficiency Secondly, the beaded structure can effectively increase the contact area between the electrode material and the electrolyte, greatly improve the embedding and extraction of ions, avoid structural collapse or destruction in the electrochemical reaction process, reduce impedance and reduce energy consumption, and thus effectively improve the conductivity and energy storage of the material; the porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material prepared by the present invention has good flexibility, high cycle stability and electronic conductivity, and can effectively avoid the volume expansion phenomenon of the electrode material; the preparation process is simple, safe and environmentally friendly, and easy to prepare on a large scale; the prepared porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material can be used in aqueous zinc ion batteries as a positive electrode, and can also be used in other ion batteries, lithium-sulfur batteries and other electrochemical and energy storage fields, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 This is a SEM image of the vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure prepared in Example 6 with an accuracy of 1000 nm; Figure 2 This is a SEM image of the vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure prepared in Example 6 with an accuracy of 100 nm; Figure 3 The charge and discharge curve of the vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure prepared in Example 6 at a current density of 0.1 a / g; Figure 4This is a rate performance diagram of the vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure prepared in Example 6 at different current densities; Figure 5 This is a long cycle performance diagram of the vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure prepared in Example 6 at a current density of 10 a / g. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the technical solutions in the embodiments of this application will be described clearly and completely in combination with the drawings in the embodiments of this application; obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0019] The present invention provides a method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, comprising the following steps: Step 1: Add polyvinyl pyrrolidone (PVP) to deionized water, and vigorously stir at 50-65° C. for 8-16 hours until the mixture is evenly stirred to obtain a uniform and stable mixed system, thereby obtaining a PVP solution.
[0020] Step 2: Mix ammonium metavanadate (NH4VO3), oxalic acid (H2C2O4) and PVP solution and react until the solution changes from orange to blue to obtain a precursor solution.
[0021] Step 3, subjecting the precursor solution to ultrasonic treatment for 1-2 hours in an ice water bath. After the ultrasonic treatment is completed, polytetrafluoroethylene emulsion (PTFE) is added to obtain a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion; wherein the mass ratio of ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion in the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is 1:2:1:(1-6).
[0022] Step 4: Mix a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion with deionized water in a mass ratio of (0.4-0.9):1, and obtain a spinning solution after ultrasonic treatment.
[0023] Step 5, using the electrospinning process, using non-woven fabric as a receiving member for the composite fiber, electrospinning the spinning solution to obtain the composite fiber; wherein, during the electrospinning process, the voltage is 12-35 kV, the ambient humidity is controlled at 40%-60%, and the temperature is controlled at 20-50°C; the speed of the collector is controlled at 500-1000 r / min; a No. 21 metal needle is used, the distance between the metal needle and the collector is 10-20 cm, and the liquid pushing speed is 10-30 μL / min.
[0024] Step 6, drying the composite fiber at 60-80° C. for 2-4 hours to obtain a dried composite fiber; Step 7: heat-treating the dried composite fiber to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure, that is, obtaining a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material.
[0025] The heat treatment process is specifically as follows: The dried composite fiber is kept at 150-250°C for 2-4 hours at a heating rate of 2-10°C / min; then, the temperature is continued to rise at a rate of 2-10°C / min and kept at 250-350°C for 2-4 hours to obtain a flexible self-supporting composite nanofiber; Then, under a protective atmosphere, the flexible self-supporting composite nanofibers are kept at 650-750° C. for 4-6 hours at a heating rate of 2-10° C. / min to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure.
[0026] Preparation principle: The method for preparing the porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material of the present invention comprises the following steps: firstly preparing a solution containing a trivalent vanadium source, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion as a spinning solution; then using an electrostatic spinning technique to prepare the spinning solution to generate composite nanofibers based on a vanadium precursor; then pre-oxidizing the spun composite nanofibers to remove residual solvents, and further heat-treating the composite nanofibers to obtain composite nanofibers with a beaded structure generated by in-situ reaction and grown by phase separation; after heat treatment in an argon atmosphere, the original polymer nanofibers are carbonized into carbon nanofibers; due to the increase in the proportion of graphite carbon, the conductivity of the carbon nanofibers is greatly improved, and the carbon nanofibers have excellent mechanical strength, which is sufficient to be used as a single electrode in electrochemical research and energy storage.
[0027] In the present invention, the prepared flexible zinc ion battery positive electrode has a special beaded microstructure, which is conducive to the full contact between the electrode material and the electrolyte. At the same time, the microscopic dispersion of the active substance of the electrode material is also improved, which is of great help to the performance improvement of the overall electrochemical energy storage device. It is worth mentioning that the microstructure of the beaded carbon fiber can greatly improve the embedding and extraction of ions, and can avoid structural collapse or damage during the electrochemical reaction process. The beaded structure of the vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode of the present invention can also be used in other electrochemical and energy storage fields such as ion batteries and lithium-sulfur batteries. In addition, the preparation process of the present invention is simple, safe and environmentally friendly, easy to prepare on a large scale, and has broad application prospects.
[0028] Example 1 This embodiment 1 provides a method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, comprising the following steps: Step 1: Add polyvinyl pyrrolidone (PVP) to deionized water, and stir vigorously at 50° C. for 8 h until the mixture is evenly stirred to obtain a uniform and stable mixed system, thereby obtaining a PVP solution.
[0029] Step 2: Mix ammonium metavanadate (NH4VO3), oxalic acid (H2C2O4) and PVP solution and react until the solution changes from orange to blue to obtain a precursor solution.
[0030] Step 3, subjecting the precursor solution to ultrasonic treatment for 1 hour in an ice-water bath, and after the completion of the ultrasonic treatment, adding polytetrafluoroethylene emulsion (PTFE) to obtain a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion; wherein the mass ratio of ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion in the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is 1:2:1:1.
[0031] Step 4: Mix a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion with deionized water in a mass ratio of 0.4:1, and obtain a spinning solution after ultrasonic treatment.
[0032] Step 5, using the electrospinning process, using non-woven fabric as a receiving member for the composite fiber, electrospinning the spinning solution to obtain the composite fiber; wherein, during the electrospinning process, the voltage is 12 kV, the ambient humidity is controlled at 40%, and the temperature is controlled at 20°C; the speed of the collector is controlled at 500 r / min; a No. 21 metal needle is used, the distance between the metal needle and the collector is 10 cm, and the liquid pushing speed is 10 μL / min.
[0033] Step 6: Dry the composite fiber at 60° C. for 2 hours to obtain a dried composite fiber.
[0034] Step 7: heat-treating the dried composite fiber to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure, that is, obtaining a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material.
[0035] The heat treatment process is specifically as follows: The dried composite fiber was kept at 150°C for 2 hours at a heating rate of 2°C / min; then, the temperature was continued to rise at 2°C / min and kept at 250°C for 2 hours to obtain a flexible self-supporting composite nanofiber; Then, under a protective atmosphere, the flexible self-supporting composite nanofibers were kept at 650°C for 4 hours at a heating rate of 2°C / min to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure.
[0036] Performance Test: The porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared in this Example 1 was experimentally tested, and the test results showed that the beaded structure porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared by electrospinning has good cycle performance and high conductivity, and can effectively reduce volume expansion, thereby improving electrochemical performance.
[0037] Example 2 This embodiment 2 provides a method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, comprising the following steps: Step 1: Add polyvinyl pyrrolidone (PVP) to deionized water, and stir vigorously at 52° C. for 10 h until the mixture is evenly stirred to obtain a uniform and stable mixed system, thereby obtaining a PVP solution.
[0038] Step 2: Mix ammonium metavanadate (NH4VO3), oxalic acid (H2C2O4) and PVP solution and react until the solution changes from orange to blue to obtain a precursor solution.
[0039] Step 3, the precursor solution is ultrasonically treated for 1.2 hours in an ice water bath. After the ultrasonic treatment is completed, polytetrafluoroethylene emulsion (PTFE) is added to obtain a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion; wherein the mass ratio of ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion in the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is 1:2:1:2.
[0040] Step 4: Mix a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion with deionized water in a mass ratio of 0.5:1, and obtain a spinning solution after ultrasonic treatment.
[0041] Step 5, using the electrospinning process, using non-woven fabric as a receiving member for the composite fiber, electrospinning the spinning solution to obtain the composite fiber; wherein, during the electrospinning process, the voltage is 16 kV, the ambient humidity is controlled at 40%, and the temperature is controlled at 25°C; the speed of the collector is controlled at 600 r / min; a No. 21 metal needle is used, the distance between the metal needle and the collector is 12 cm, and the liquid pushing speed is 15 μL / min.
[0042] Step 6: Dry the composite fiber at 65° C. for 2.5 hours to obtain a dried composite fiber.
[0043] Step 7: heat-treating the dried composite fiber to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure, that is, obtaining a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material.
[0044] The heat treatment process is specifically as follows: The dried composite fiber was kept at 170°C for 2.5 hours at a heating rate of 4°C / min; then, the temperature was continued to rise at 4°C / min and kept at 270°C for 2.5 hours to obtain a flexible self-supporting composite nanofiber; Then, under a protective atmosphere, the flexible self-supporting composite nanofibers were kept at 670°C for 4.5 hours at a heating rate of 4°C / min to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure.
[0045] Performance Test: The porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared in this Example 2 was experimentally tested, and the test results showed that the beaded structure porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared by electrospinning has good cycle performance and high conductivity, and can effectively reduce volume expansion, thereby improving electrochemical performance.
[0046] Example 3 This embodiment 3 provides a method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, comprising the following steps: Step 1: Add polyvinyl pyrrolidone (PVP) to deionized water, and stir vigorously at 56° C. for 12 h until the mixture is evenly stirred to obtain a uniform and stable mixed system, thereby obtaining a PVP solution.
[0047] Step 2: Mix ammonium metavanadate (NH4VO3), oxalic acid (H2C2O4) and PVP solution and react until the solution changes from orange to blue to obtain a precursor solution.
[0048] Step 3, the precursor solution is ultrasonically treated for 1.4 hours in an ice water bath. After the ultrasonic treatment is completed, polytetrafluoroethylene emulsion (PTFE) is added to obtain a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion; wherein the mass ratio of ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion in the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is 1:2:1:3.
[0049] Step 4: Mix a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion with deionized water in a mass ratio of 0.6:1, and obtain a spinning solution after ultrasonic treatment.
[0050] Step 5, using the electrospinning process, using non-woven fabric as a receiving member for the composite fiber, electrospinning the spinning solution to obtain the composite fiber; wherein, during the electrospinning process, the voltage is 18 kV, the ambient humidity is controlled at 50%, and the temperature is controlled at 30°C; the speed of the collector is controlled at 700 r / min; a No. 21 metal needle is used, the distance between the metal needle and the collector is 14 cm, and the liquid pushing speed is 20 μL / min.
[0051] Step 6, drying the composite fiber at 70° C. for 3 hours to obtain a dried composite fiber; Step 7: heat-treating the dried composite fiber to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure, that is, obtaining a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material.
[0052] The heat treatment process is specifically as follows: The dried composite fiber was kept at 200°C for 3 hours at a heating rate of 6°C / min; then the temperature was continued to rise at 300°C for 3 hours at a heating rate of 6°C / min to obtain a flexible self-supporting composite nanofiber; Then, under a protective atmosphere, the flexible self-supporting composite nanofibers were kept at 690°C for 5 hours at a heating rate of 6°C / min to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure.
[0053] Performance Test: The porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared in Example 3 was experimentally tested, and the test results showed that the beaded structure porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared by electrospinning has good cycle performance and high conductivity, and can effectively reduce volume expansion, thereby improving electrochemical performance.
[0054] Example 4 This embodiment 4 provides a method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, comprising the following steps: Step 1: Add polyvinyl pyrrolidone (PVP) to deionized water, and stir vigorously at 58° C. for 14 h until the mixture is evenly stirred to obtain a uniform and stable mixed system, thereby obtaining a PVP solution.
[0055] Step 2: Mix ammonium metavanadate (NH4VO3), oxalic acid (H2C2O4) and PVP solution and react until the solution changes from orange to blue to obtain a precursor solution.
[0056] Step 3, the precursor solution is ultrasonically treated for 1.6 hours in an ice water bath. After the ultrasonic treatment is completed, polytetrafluoroethylene emulsion (PTFE) is added to obtain a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion; wherein the mass ratio of ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion in the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is 1:2:1:4.
[0057] Step 4: Mix a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion with deionized water in a mass ratio of 0.7:1, and obtain a spinning solution after ultrasonic treatment.
[0058] Step 5, using the electrospinning process, using non-woven fabric as a receiving member for the composite fiber, electrospinning the spinning solution to obtain the composite fiber; wherein, during the electrospinning process, the voltage is 24 kV, the ambient humidity is controlled at 55%, and the temperature is controlled at 35°C; the speed of the collector is controlled at 800 r / min; a No. 21 metal needle is used, the distance between the metal needle and the collector is 16 cm, and the liquid pushing speed is 25 μL / min.
[0059] Step 6, drying the composite fiber at 70° C. for 3.5 hours to obtain a dried composite fiber; Step 7: heat-treating the dried composite fiber to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure, that is, obtaining a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material.
[0060] The heat treatment process is specifically as follows: The dried composite fiber was kept at 210°C for 3 hours at a heating rate of 8°C / min; then the temperature was continued to rise at 8°C / min and kept at 310°C for 3 hours to obtain a flexible self-supporting composite nanofiber; Then, under a protective atmosphere, the flexible self-supporting composite nanofibers were kept at 710°C for 5.5 hours at a heating rate of 8°C / min to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure.
[0061] Performance Testing: The porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared in this Example 4 was experimentally tested, and the test results showed that the beaded structure porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared by electrospinning has good cycle performance and high conductivity, and can effectively reduce volume expansion, thereby improving electrochemical performance.
[0062] Example 5 This embodiment 5 provides a method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, comprising the following steps: Step 1: Add polyvinyl pyrrolidone (PVP) to deionized water, and stir vigorously at 62° C. for 15 h until the mixture is evenly stirred to obtain a uniform and stable mixed system, thereby obtaining a PVP solution.
[0063] Step 2: Mix ammonium metavanadate (NH4VO3), oxalic acid (H2C2O4) and PVP solution and react until the solution changes from orange to blue to obtain a precursor solution.
[0064] Step 3, the precursor solution is ultrasonically treated for 1.8 hours in an ice water bath. After the ultrasonic treatment is completed, polytetrafluoroethylene emulsion (PTFE) is added to obtain a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion; wherein the mass ratio of ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion in the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is 1:2:1:5.
[0065] Step 4: Mix a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion with deionized water in a mass ratio of 0.8:1, and obtain a spinning solution after ultrasonic treatment.
[0066] Step 5, using the electrospinning process, using non-woven fabric as a receiving member for the composite fiber, electrospinning the spinning solution to obtain the composite fiber; wherein, during the electrospinning process, the voltage is 28 kV, the ambient humidity is controlled at 55%, and the temperature is controlled at 45°C; the speed of the collector is controlled at 900 r / min; a No. 21 metal needle is used, the distance between the metal needle and the collector is 18 cm, and the liquid pushing speed is 25 μL / min.
[0067] Step 6, drying the composite fiber at 75° C. for 3.5 hours to obtain a dried composite fiber; Step 7: heat-treating the dried composite fiber to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure, that is, obtaining a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material.
[0068] The heat treatment process is specifically as follows: The dried composite fiber was kept at 230°C for 3.5 hours at a heating rate of 8°C / min; then the temperature was continued to rise at 330°C for 5.5 hours at a heating rate of 8°C / min to obtain a flexible self-supporting composite nanofiber; Then, under a protective atmosphere, the flexible self-supporting composite nanofibers were kept at 730°C for 6 hours at a heating rate of 8°C / min to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure.
[0069] Performance Test: The porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared in this Example 5 was experimentally tested, and the test results showed that the beaded structure porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared by electrospinning has good cycle performance and high conductivity, and can effectively reduce volume expansion, thereby improving electrochemical performance.
[0070] Example 6 This embodiment 6 provides a method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, comprising the following steps: Step 1: Add polyvinyl pyrrolidone (PVP) to deionized water, and stir vigorously at 65° C. for 16 h until the mixture is evenly stirred to obtain a uniform and stable mixed system, thereby obtaining a PVP solution.
[0071] Step 2: Mix ammonium metavanadate (NH4VO3), oxalic acid (H2C2O4) and PVP solution and react until the solution changes from orange to blue to obtain a precursor solution.
[0072] Step 3, subjecting the precursor solution to ultrasonic treatment for 2 hours in an ice-water bath. After the ultrasonic treatment is completed, polytetrafluoroethylene emulsion (PTFE) is added to obtain a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion; wherein the mass ratio of ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion in the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is 1:2:1:6.
[0073] Step 4: Mix a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion with deionized water in a mass ratio of 0.9:1, and obtain a spinning solution after ultrasonic treatment.
[0074] Step 5, using the electrospinning process, using non-woven fabric as a receiving member for the composite fiber, electrospinning the spinning solution to obtain the composite fiber; wherein, during the electrospinning process, the voltage is 35 kV, the ambient humidity is controlled at 50%, and the temperature is controlled at 50°C; the speed of the collector is controlled at 1000 r / min; a No. 21 metal needle is used, the distance between the metal needle and the collector is 20 cm, and the liquid pushing speed is 30 μL / min.
[0075] Step 6, drying the composite fiber at 80° C. for 4 hours to obtain a dried composite fiber; Step 7: heat-treating the dried composite fiber to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure, that is, obtaining a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material.
[0076] The heat treatment process is specifically as follows: The dried composite fiber was kept at 250°C for 4 hours at a heating rate of 10°C / min; then, the temperature was continued to rise at 350°C for 4 hours at a heating rate of 10°C / min to obtain a flexible self-supporting composite nanofiber; Then, under a protective atmosphere, the flexible self-supporting composite nanofibers were kept at 750°C for 6 hours at a heating rate of 10°C / min to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure.
[0077] Performance Test: The porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared in Example 6 was experimentally tested, and the test results showed that the beaded structure porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared by electrospinning has good cycle performance and high conductivity, and can effectively reduce volume expansion, thereby improving electrochemical performance.
[0078] As attached Figure 1As shown, attached Figure 1 The SEM image of the vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure prepared in Example 6 with an accuracy of 1000 nm is given in the attached Figure 2 The SEM image of the vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure prepared in Example 6 with an accuracy of 100 nm is given in the attached Figure 1-2 It can be seen that after carbonization, the fiber surface has a bead-like structure, which can further increase the contact between the electrolyte and the electrode.
[0079] As attached Figure 3 As stated, attached Figure 3 The charge and discharge curves of the vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure prepared in Example 6 at a current density of 0.1 a / g are given in the accompanying drawings. Figure 3 It can be seen that at low current density, the prepared electrode material has a higher specific capacity, reaching 390mah / g.
[0080] As attached Figure 4 As stated, attached Figure 4 The rate performance diagram of the vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure prepared in Example 6 at different current densities is given in the attached figure. Figure 4 It can be seen that at current densities of 0.5A / g, 0.7A / g, 1A / g, 3A / g, 5A / g, 7A / g, 10A / g, 15A / g and 20A / g, the discharge specific capacity of the electrode is 349.5mAh / g, 321.1mAh / g, 302.1mAh / g, 221.7mAh / g, 174.9mAh / g, 151.1mAh / g, 130mAh / g, 105.4mAh / g and 88.3mAh / g, respectively, showing excellent charge and discharge specific capacity and good capacity retention rate.
[0081] As attached Figure 5 As stated, attached Figure 5 The long cycle performance diagram of the vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure prepared in Example 6 at a current density of 10 a / g is given in the figure; Figure 5 It can be seen that with the increase of the number of cycles, the capacity hardly decreases, indicating that the electrode has good cycle stability; the reason is that the beaded structure of the electrode keeps the capacity unchanged when zinc ions are embedded and removed during the charge and discharge process. On the one hand, the carbon skeleton provides an expandable volume, and on the other hand, it improves the cycle stability of the material.
[0082] The preparation method of the porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material of the present invention adopts an electrostatic spinning process for preparation, and water is used as a solvent for electrostatic spinning, which is safe and green. PVP is used as a flexible substrate support for the carbon source, and then the PVP is carbonized by a high-temperature carbonization process. The carbonized PVP can be used as a reinforcing agent and conductive material to improve the electrode stability. The precursor salt is made to generate active substances in the carbon skeleton in situ, giving an efficient carbon fiber skeleton conductive network. At the same time, the beaded structure also has a good improvement effect on its conductivity and energy storage. A flexible, conductive, lightweight, high-rate, and excellent cycle performance zinc ion battery positive electrode material is prepared.
[0083] The porous vanadium-based composite carbon nanofiber flexible zinc-ion battery positive electrode material prepared in the present invention has a beaded structure vanadium-based composite carbon nanofiber flexible electrode material with a special microstructure, and the microstructure can increase the contact area between the electrode material and the electrolyte, reduce impedance, and reduce energy consumption; the electrode material has a unique carbon skeleton support, which improves the electrochemical stability of the positive electrode material; water is used as the spinning solvent in the preparation process, which can reduce pollution during the spinning process and conforms to the concept of green chemistry; the beaded V2O3@CNFs electrode material prepared by the electrospinning method has good flexibility and high zinc ion storage performance.
[0084] The above embodiment is only one of the implementation methods that can realize the technical solution of the present invention. The scope of protection claimed by the present invention is not limited only to this embodiment, but also includes changes, replacements and other implementation methods that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention.
Claims
1. A method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, characterized in that: include: A pre-prepared uniform solution containing ammonium metavanadate, dihydrated oxalic acid, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is added into deionized water and subjected to ultrasonic treatment to obtain a spinning solution; Electrospinning the spinning solution to obtain composite fibers; drying the composite fiber to obtain a dried composite fiber; The dried composite fibers are heat-treated to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure, that is, a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material.
2. The method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material according to claim 1, characterized in that: The mass ratio of the uniform solution containing ammonium metavanadate, dihydrated oxalic acid, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion to deionized water is (0.4-0.9):
1.
3. The method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material according to claim 2, characterized in that: In the uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion, the mass ratio of ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is 1:2:1:(1-6).
4. The method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material according to claim 1, characterized in that: The preparation process of the uniform solution containing ammonium metavanadate, dihydrated oxalic acid, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion is as follows: Add PVP to deionized water and stir vigorously until uniform to obtain a PVP solution; ammonium metavanadate, oxalic acid and PVP solution are mixed and reacted to obtain a precursor solution; The precursor solution is subjected to ultrasonic treatment in an ice water bath. After the ultrasonic treatment is completed, polytetrafluoroethylene emulsion is added to obtain a uniform solution containing ammonium metavanadate, oxalic acid dihydrate, polyvinyl pyrrolidone and polytetrafluoroethylene emulsion.
5. The method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material according to claim 1, characterized in that: During the electrospinning of the spinning solution to obtain the composite fiber, the voltage is 12-35 kV, the ambient humidity is controlled at 40%-60%, the distance between the metal needle and the collector is 10-20 cm, and the temperature is controlled at 20-50°C.
6. The method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material according to claim 1, characterized in that: In the process of electrostatically spinning the spinning solution to obtain the composite fiber, the non-woven fabric is used as a receiving member for the composite fiber.
7. The method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material according to claim 1, characterized in that: The composite fiber is dried to obtain the dried composite fiber at a drying temperature of 60-80° C. and a drying time of 2-4 hours.
8. The method for preparing a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material according to claim 1, characterized in that: The process of heat treatment of the dried composite fiber is as follows: The dried composite fiber is kept at 150-250°C for 2-4 hours at a heating rate of 2-10°C / min; then, the temperature is continued to rise at a rate of 2-10°C / min and kept at 250-350°C for 2-4 hours to obtain a flexible self-supporting composite nanofiber; Then, under a protective atmosphere, the flexible self-supporting composite nanofibers are kept at 650-750° C. for 4-6 hours at a heating rate of 2-10° C. / min to obtain a vanadium trioxide-based composite carbon nanofiber flexible electrode material with a beaded structure.
9. A porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material, characterized in that: The porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material is prepared by the preparation method of any one of claims 1 to 8.
10. The use of a porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material as claimed in claim 9, characterized in that: The porous vanadium-based composite carbon nanofiber flexible zinc ion battery positive electrode material is used in an aqueous zinc ion battery and serves as the positive electrode of the aqueous zinc ion battery.
Citation Information
Patent Citations
Preparation method of carbon-coated vanadate composite fiber for lithium-ion battery anode material
CN102280625A
Vanadium nitride (VN) porous hollow nano-fiber and preparation method thereof
CN104532405A
Mesoporous nanofiber sodium vanadium fluorophosphate positive electrode material and preparation method thereof
CN113293459A
Preparation method of lithium ion battery material LiF-V2O3 / C
CN115472792A
Flexible self-supporting vanadium heptacarbide / nitrogen-doped porous carbon nanofiber composite material as well as preparation method and application of flexible self-supporting vanadium heptacarbide / nitrogen-doped porous carbon nanofiber composite material
CN116111064A
